2006
DOI: 10.1111/j.1528-1167.2006.00875.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Outcome of Pattern‐Sensitive Epilepsy

Abstract: Summary:Purpose: To evaluate the long-term outcome of patients with pattern-sensitive epilepsy.Methods: We prospectively studied 35 patients (21 females and 14 males) with pattern-sensitive epilepsy (follow up ≥5 years; mean 13.9; range 6.4 -27.6). All cases had regular clinical examinations and serial electroencephalographic (EEG) recordings. Photosensitivity and pattern sensitivity were ascertained neurophysiologically in all cases. Outcome was evaluated according to the following variables: duration of phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…The first peak of seizures being more frequent in the first few years of life while a second and more pronounced peak among subjects with age more than 65 years. 22,23 This variation in the current study from developed world could be due to major population falling with-in age-group of 25-40 years as compared to elderly population. The other factor could be that in elderly people, seizures are neglected as compared to young population.…”
Section: Discussionmentioning
confidence: 77%
“…The first peak of seizures being more frequent in the first few years of life while a second and more pronounced peak among subjects with age more than 65 years. 22,23 This variation in the current study from developed world could be due to major population falling with-in age-group of 25-40 years as compared to elderly population. The other factor could be that in elderly people, seizures are neglected as compared to young population.…”
Section: Discussionmentioning
confidence: 77%
“…On the other hand, the changes in response to IPS were not significantly related to the reduction in frequency of DWM. This dichotomy could be due to the underlying process of epileptogenesis which in the case of PPR implies a genetically determined cortical hyperexcitability related to specific sensory inputs (Brinciotti et al, 2006). These findings are consistent with earlier case reports or small patient group reports using levetiracetam as adjunctive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that pattern sensitive epilepsy is a distinguishable subtype of PSE in which the excitable regions within the visual cortex concerned with different attributes of observed objects or patterns determine susceptibility to a specific trigger and result in an electro clinical response [29]. The long-term outcome of patients with pattern-sensitive epilepsy was analysed by Brinciotti et al [30]. Generalised seizures were the most common type of spontaneous seizures (60%) whereas reflex seizures were more frequently partial (74%) [30].…”
Section: Epidemiological Aspectsmentioning
confidence: 99%
“…The long-term outcome of patients with pattern-sensitive epilepsy was analysed by Brinciotti et al [30]. Generalised seizures were the most common type of spontaneous seizures (60%) whereas reflex seizures were more frequently partial (74%) [30]. At the end of follow-up, 80% of the patients had been seizure-free for more than two years [30].…”
Section: Epidemiological Aspectsmentioning
confidence: 99%